2006
DOI: 10.1111/j.1365-4632.2004.02398.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maintenance narrow‐band ultraviolet B therapy on the duration of remission for psoriasis: a prospective randomized clinical trial

Abstract: The results provide some evidence that maintenance narrow-band UVB may achieve longer remission durations for patients with plaque-type psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
1
18
1
2
Order By: Relevance
“…The very good response of adult AGP to NB-UVB in our study exceeds the results obtained with biologics in psoriasis [18] and suggested that NB-UVB should be the first line of treatment of AGP according to guidelines [7][8][9] , but it also raised a number of variables to consider when AGP is evaluated together with plaquetype psoriasis. This was the reason for analyzing other data in our group of patients.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The very good response of adult AGP to NB-UVB in our study exceeds the results obtained with biologics in psoriasis [18] and suggested that NB-UVB should be the first line of treatment of AGP according to guidelines [7][8][9] , but it also raised a number of variables to consider when AGP is evaluated together with plaquetype psoriasis. This was the reason for analyzing other data in our group of patients.…”
Section: Discussioncontrasting
confidence: 42%
“…No concomitant treatment and no maintenance treatment were applied because of the good results (88% of CR in 18 months) although a recent study provides some evidence that maintenance with NB-UVB in plaque-type psoriasis may achieve a longer remission [18] . The very good response of adult AGP to NB-UVB in our study exceeds the results obtained with biologics in psoriasis [18] and suggested that NB-UVB should be the first line of treatment of AGP according to guidelines [7][8][9] , but it also raised a number of variables to consider when AGP is evaluated together with plaquetype psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Remission times were prolonged using maintenance therapy. [26][27][28] The advent of NB-UVB lamps improved the use of UVB therapy in psoriasis and is widely considered to be preferable to BB-UVB therapy. NB-UVB use was initially popularized in the United Kingdom and Europe in the mid-1980s, and became available in the United States approximately one decade later.…”
Section: Efficacymentioning
confidence: 99%
“…13 Although some evidence suggests that maintenance NB-UVB therapy may achieve longer remission durations in patients with plaque-type psoriasis, there is no general consensus regarding the utility of long-term maintenance with NB-UVB. 43 PUVA. The implementation of UVA phototherapy plus psoralen (PUVA) dates back thousands of years to the treatment of patients with vitiligo in ancient Egypt.…”
Section: Clinical Datamentioning
confidence: 96%